International Paediatric Stroke Study: stroke associated with cardiac disorders. (11th December 2012) - Dowling, Michael M.; Hynan, Linda S.; Lo, Warren; Licht, Daniel J.; McClure, Chalmer; Yager, Jerome Y.; Dlamini, Nomazulu; Kirkham, Fenella J.; deVeber, Gabrielle; Pavlakis, Steve; ,
Abstract : Background and hypothesis: The aetiologies of arterial ischaemic stroke in children are diverse and often multifactorial. A large proportion occurs in children with cardiac disorders. We hypothesized that the clinical and radiographic features of children with arterial ischaemic stroke attributed to cardiac disorders would differ from those with other causes. Methods: Using the large population collected in the prospective International Paediatric Stroke Study, we analysed the characteristics, clinical presentations, imaging findings, and early outcomes of children with and without cardiac disorders. Results: Aetiological data were available for 667 children with arterial ischaemic stroke (ages 29 days to 19 years). Cardiac disorders were indentified in 204/667 (30·6%), congenital defects in 121/204 (59·3%), acquired in 40/204 (19·6%), and isolated patent foramen ovale in 31/204 (15·2%). Compared to other children with stroke, those with cardiac disorders were younger (median age 3·1 vs. 6·5 years; P < 0·001) and less likely to present with headache (25·6% vs. 44·6%; P < 0·001), but were similar in terms of gender and presentation with focal deficits, seizures, or recent infection. Analysis of imaging data identified significant differences ( P = 0·005) in the vascular distribution (anterior vs. posterior circulation or both) between groups. Bilateral strokes and haemorrhagic conversion were more prevalent in the cardiac disorders group. Conclusions: Cardiac disorders were identified in almost one‐third of children with arterial ischaemic stroke. They had similar clinical presentations to those without cardiac disorders but differed in age and headache prevalence. Children with cardiac disorders more frequently had a 'cardioembolic stroke pattern' with a higher prevalence of bilateral strokes in both the anterior and posterior circulations, and a greater tendency to haemorrhagic transformation.